2004
DOI: 10.1111/j.1538-7836.2004.00842.x
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in the prevention of venous thromboembolism in the elderly

Abstract: Summary. Aging itself is a risk factor for venous thromboembolism, and the prevalence in the elderly of additional risk factors (e.g. cancer, orthopedic surgery, immobility) increase its intrinsic risk. Many in the medical community are reluctant to prescribe anticoagulation (for primary and secondary prevention of venous thromboembolism) to their geriatric patients for the fear that bleeding complications may outweigh the benefits. A thorough analysis of the data support the concept that the under-use of hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 61 publications
1
25
0
3
Order By: Relevance
“…[2][3][4]. Comparison between data waiting and mortality showed an increase of mortality in some way associated to the diagnostic data timing of supply, with an Data related to mortality and morbidity of TE linked to the specialty of the clinical departments where patients are treated were taken into consideration.…”
Section: Medical Treatment Before and After Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4]. Comparison between data waiting and mortality showed an increase of mortality in some way associated to the diagnostic data timing of supply, with an Data related to mortality and morbidity of TE linked to the specialty of the clinical departments where patients are treated were taken into consideration.…”
Section: Medical Treatment Before and After Surgerymentioning
confidence: 99%
“…2 However, because of the variety of risk factors in these patients and their individual health problems (e.g., comorbidities, therapies), 3 the guidelines formulated for these cases are scarcely applied. The type of procedure as well as trauma are crucial for VTE in surgical patients (general surgery, gynecology, and orthopedics).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that bleeding from antithrombotic agents is a strong predictor of mortality and reduces the overall benefits of VTE prophylaxis in hospitalized patients (14,(45)(46)(47)(48).…”
Section: Contraindications To Prophylaxismentioning
confidence: 99%
“…We read with interest the articles by Minno and Tufano (2004) and Zakai et al (2004), which serve to highlight the need for prevention of venous thromboembolism (VTE) in at-risk patients. We recently audited our use of prophylactic low molecular weight heparin (LMWH) in hospitalized older adults (65 years or older) over a 6-week period.…”
mentioning
confidence: 99%
“…VAN The 2-year cumulative recurrence rate of deep venous thrombosis after suffering a single episode of thrombosis is approximately 10%-18% [1,2]. Recently, it was shown that the risk of recurrent venous thrombosis is higher among men than women, a difference that appeared not to be due to discontinuation of oral contraceptives or hormone replacement therapy, the presence of the factor V Leiden (FV Leiden) or the prothrombin mutation, or elevated levels of factor VIII or IX (FVIII or FIX) [3,4].…”
mentioning
confidence: 99%